Eating habits among the Omsk Oblast population and poor nutrition in association with cardiovascular diseases according to the ESSE-RF2 study - I. A. Viktorova; V. L. Stasenko; N. G. Shirlina; G. A. Muromtseva; M. A. Livzan (Российский кардиологический журнал, 2021)
Aim. To assess the prevalence of eating habits among the Omsk Oblast population and their association with cardiovascular diseases (CVDs) according to the ESSERF2 study.Material and methods. In the ESSE-RF2 study with persons aged 25-64 years (random sample, n=1648), the dietary habits of 21 food groups were assessed using the questionnaire method. Results. Insufficient consumption of vegetables and fruits was revealed in 60,0% and 68,7% of the region’s population, which is 1,5-2,2 times higher than amongRussians. The daily intake of cereals is 2,3 times higher than that of pasta, especially in those with CVDs. In the region, poultry is preferred. Poultry at least once a week is consumed by 91,7% of Omsk residents, red meat — 74,8%, and fish — only 35,2% (vs 84,7%, 83,1% and 65,1% in Russians, respectively). The daily intake of liquid dairy products is low. Cheese and cottage cheese is consumed significantly lower than the national average, while legumes — 4 times lower. The presence of confectionery in the daily diet of 40,3% of Omsk residents looks more favorable than the average among Russians. In addition, 50% of the population eat pickles only 1-2 times a month (significantly less than in Russia). On the contrary, 60,9% of Omsk residents regularly (daily-weekly) consume meat and sausages (56,0% in Russia, p=0,000). Omsk residents with CVDs refrain from excessive consumption of sugar, other sweets, meat and sausages, pickles and marinades. They are almost 2 times more likely to exclude red meat from the diet or reduce its daily consumption than people without CVDs. Salting of cooked food, consumption of vegetables and fruits, fish, seafood and dairy products practically did not depend on CVDs.Conclusion. The food habits of Omsk residents differs from the national one in many products. People with CVDs have unfavorable eating habits: reduced consumption of fresh vegetables, fruits, fish, seafood, legumes and nuts. Patients do not change their diet in favor of cardioprotective products and decrease in adding more salt. Although, they more often refuse meat and sausages, pickles, marinades, sweets, and pasta, and increase the consumption of cereals.